Customer customer satisfaction and the determinants of firm value: a case for JSE listed firms - Nteyi, Busisiwe (My University, 2023)
This study examines the relationship of the South African Customer Satisfaction Index (SACSI) and the determinants of firm value for South African listed firms. The American Customer Satisfaction Index (ACSI) has been a subject for research for over two decades in the United States, yet the effect of the SACSI created from adopting the ACSI methodology has not been examined. The study is intended to contribute to marketing literature in South Africa by being the first to examine the SACSI. The study aims to establish if there are relationships between the SACSI and determinants of firm value presented by return on assets, future cash flow, financial leverage, and Tobin’s Q. The study adopted a quantitative method using longitudinal data of Johannesburg Stock Exchange listed firms. The customer satisfaction index scores and financial and stock market data were collected for eight years from 2013 to 2020 and analysed using Stata, a statistical software package. The sample size consisted of 25 listed firms. The findings reveal that customer satisfaction has no effect on the determinants of firm value in the South African context. Implication and suggestions for future research are discussed
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: South African customer satisfaction index; JSE listed firms; Customer satisfaction; SDG-8: Decent work and economic growth